ANALISIS LAJU PERTUMBUHAN DAN EFEKTIVITAS PENERIMAAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN DI KOTA PALEMBANG - Meisya, Meisya; Sandrayati, Sandrayati; Mubarok, Muhammad Husni (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to analyze the growth and effectiveness of taxes on non-metallic minerals and rocks in Palembang City from 2019 to 2023. This research uses a descriptive approach with qualitative methods. Data obtained through interviews as primary data and secondary data target and realization of Palembang City Regional Tax for 2019 - 2023. The results of this research explain that during the period 2019 to 2023 the growth rate of Non-Metal Mineral and Rock Tax for Palembang City has an average value amounted to 11.22% and was categorized as unsuccessful. On the effectiveness side, it shows that during the period 2019 to 2023 the effectiveness of non-metallic mineral and rock taxes in Palembang City is included in the effective category with an average effectiveness value of 91.17%.